2023
DOI: 10.3390/v15061250
|View full text |Cite
|
Sign up to set email alerts
|

ZIKV Strains Elicit Different Inflammatory and Anti-Viral Responses in Microglia Cells

Abstract: In recent years, the Zika Virus (ZIKV) has caused pandemic outbreaks associated with a high rate of congenital ZIKV syndrome (CZS). Although all strains associated with worldwide outbreaks derive from the Asian lineage, the reasons for their enhanced spread and severity are not fully understood. In this study, we conducted a comparative analysis of miRNAs (miRNA-155/146a/124) and their cellular targets (SOCS1/3, SHP1, TRAF6, IRAK1), as well as pro- and anti-inflammatory and anti-viral cytokines (IL-6, TNF-α, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Remarkably, while extensive differences were seen at the level of the miRNA, the strain type-specific effects were also seen at the protein level of a selected putative target, HSP70. The results from this study and others [69,71,72,76] indicate that future studies on the modulation of miRNAs as a consequence of ZIKV infection must take into account strain type variation, as the results generated by a single strain will be of limited value in understanding the role of miRNAs in ZIKV infection.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Remarkably, while extensive differences were seen at the level of the miRNA, the strain type-specific effects were also seen at the protein level of a selected putative target, HSP70. The results from this study and others [69,71,72,76] indicate that future studies on the modulation of miRNAs as a consequence of ZIKV infection must take into account strain type variation, as the results generated by a single strain will be of limited value in understanding the role of miRNAs in ZIKV infection.…”
Section: Discussionmentioning
confidence: 77%
“…A number of studies have previously investigated the involvement of miRNAs in ZIKV infection [24,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. These studies have variously identified the regulation of miR-302b, miR-302c, miR-194 and miR-30c in ZIKV-infected human NPCs in vitro [73], miR-146a in ZIKV-infected human microglial cells [75], hsa-miR-101-3p in ZIKV-infected human brain microvascular endothelial cells [67], mir-204 in human fetal neural stem cells as a consequence of ZIKV E protein expression [66], miR-7013-5p in ZIKV-infected fetal mouse neurons [62], miR-9 in ZIKV-infected mice [24] and miR-30e-3p, miR-30e-5p and miR-17-5p in ZIKV-infected astrocytes [70].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For pregnant women, most ZIKV infections are asymptomatic; however, mother-to-child transmission of the virus may result in severe fetal and childhood defects such as microcephaly, lissencephaly, cortical calcifications, uveitis, and unilateral acute maculopathy. For adults, ZIKV infection may cause Guillain–Barré syndrome (GBS) (Oliveira et al 2023 , Olmo et al 2023 ). Moreover, the viral RNA encodes a polypeptide precursor, and its amino terminus 1/3 produces three structural proteins, which are present in the envelope (E), premembrane/membrane (prM/M), and capsid (C) of the virion.…”
Section: Introductionmentioning
confidence: 99%